Studi Analisis Kemampuan Metakognitif Siswa Sekolah Dasar - Syamsurijal; Azaz Akbar (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
Metacognitive skills are higher-order thinking skills that play a crucial role in supporting the academic success of elementary school students. Previous research indicates that metacognition contributes positively to learning outcomes, problem-solving abilities, and self-regulated learning. However, most studies have been partial, focusing only on specific subjects, utilizing quantitative approaches, and failing to provide a comprehensive synthesis of the overall development and characteristics of metacognitive abilities. This study aims to systematically analyze the metacognitive abilities of elementary school students, including their characteristics, learning strategies, and implications for learning processes and outcomes. This research employs a qualitative approach using the Systematic Literature Review (SLR) method. Data sources were gathered from national and international scientific articles published between 2020 and 2025 through the Google Scholar database, DOAJ, and accredited journals. A total of 15 relevant articles were analyzed through the stages of identification, selection, data extraction, and synthesis of research findings. The results show that the metacognitive abilities of elementary school students are in the developing category and can be significantly improved through the implementation of learning strategies that emphasize planning, monitoring, and evaluating the learning process. Learning strategies such as problem-based learning, discovery learning, reflective learning, and the use of metacognitive-based student worksheets (LKPD) have proven effective in enhancing students' thinking awareness and self-regulated learning. These findings underscore the importance of integrating metacognitive strategies into teaching to support the development of higher-order thinking skills.